KONSTRUKSI KONSEP AKUNTANSI ISLAM: Suatu Upaya Membangun Akuntansi Humanis - Ahamad Fahrudin Alamsyah (El Harakah, 2008)
The economy of capitalism is born out of a view that the prosperity of society can only be achieved if the production activity is left to the individual who is detached from the ties of moral, spiritual values, so as to wriggle all his desires. Conventional accounting developed within the capitalist mindset, certainly not apart from the values of capitalism which became the basis of the concept/theory used. Islamic accounting is a new technology that shows that the social, moral, and economic value of Islam becomes an important concern in determining the principles that will be developed. Accounting methods that cover all accounting principles that govern the community as a whole. Islamic accounting ultimately depends on the goal to be achieved by a perfect Islamic society. Islamic accounting will be able to contribute greatly to the progress of world accounting. Islam as rahmatan lil 'alamin should also provide an accounting concept that provides benefits to all of nature.